The resolution of hypertrophic pulmonary osteoarthropathy following treatment of subacute infective endocarditis. Issue 657 (July 1980) - Shapiro, L. M.; Mackinnon, J.
Abstract : A patient with a corrected coarctation of the aorta subsequently developed infective endocarditis on a congenital bicuspid aortic valve. Resolution of the radiographic bone changes of hypertrophic pulmonary osteoarthropathy was demonstrated following treatment of the infection.